2022
DOI: 10.3390/min12030295
|View full text |Cite
|
Sign up to set email alerts
|

Geometallurgy of Cobalt Black Ores in the Katanga Copperbelt (Ruashi Cu-Co Deposit): A New Proposal for Enhancing Cobalt Recovery

Abstract: Copper-cobalt deposits in the Central African Copperbelt belong to the Sediment-Hosted Stratiform Copper (SHSC) type and are situated in the Neoproterozoic Katanga Supergroup. This paper describes in detail the geology, geochemistry and hydrometallurgy of cobalt, with a special focus on the Black Ore Mineralised Zone (BOMZ) unit from the Ruashi Cu-Co deposit as a case study. Based on results from fieldwork and laboratory testing, it was concluded that the BOMZ consists of a succession of massive and stratified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…As observed by the characterization of the cell battery, there is a high concentration of Co (21.1%), which is at least 50 times higher than that in natural sources. 34,35 The cathode material represents 35.4% of the cell battery, which is the main economic value. It is estimated that 87% of the economic value is due to the Co content, where for each ton of this cell battery, up to US$ 12,769 may be recovered, 90% of the cathode.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As observed by the characterization of the cell battery, there is a high concentration of Co (21.1%), which is at least 50 times higher than that in natural sources. 34,35 The cathode material represents 35.4% of the cell battery, which is the main economic value. It is estimated that 87% of the economic value is due to the Co content, where for each ton of this cell battery, up to US$ 12,769 may be recovered, 90% of the cathode.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…These results confirmed that the removal of Fe, together with As, was achieved under hydrothermal conditions with no significant removal of the other metals. The remaining solutions can be utilized to further refine the contained metals such as Cu, Zn, and Co ,, or to directly isolate them by precipitation or electrodeposition (e.g., electrowinning). , …”
Section: Resultsmentioning
confidence: 99%
“…In hydrometallurgical methods, use of chemicals in aqueous solution for metal extraction is often the practice . The most commonly used chemicals are ammonia, ,,, or other bases, acids and their salts, as well as oxidation agents , that enable selective leaching of the targeted metals from either pretreated or untreated material. On the other hand, pure water is seldom used as a lixiviant due to its low selectivity and poor mineral solubility. , …”
Section: Introductionmentioning
confidence: 99%
“…Mining activities in the Katangese Copperbelt (KCB, DR Congo) for more than a century generated great quantities of mining waste. These result from ore extraction in mines and metallurgical processes for ore purification; a typology of mining waste in the KCB is provided in the literature [1][2][3]. Mining is responsible for metal dissemination and the related pollution of the environment, as reported by numerous studies.…”
Section: Introductionmentioning
confidence: 99%